2008
DOI: 10.4028/www.scientific.net/msf.600-603.1281
|View full text |Cite
|
Sign up to set email alerts
|

Semipolar Nitrides Grown on Si(001) Offcut Substrates with 3C-SiC Buffer Layers

Abstract: The growth process of semipolar GaN(10-12) on Si(001) offcut substrates with 3C-SiC buffer layers has been investigated. From XRD analysis, the difference in the crystal orientation between GaN(10-12) and 3C-SiC(001) has been found to be around 8˚ toward the [110] direction of the 3C-SiC templates. From TEM observations, a cubic-phase AlN seed layer is found to grow on 3C-SiC(001) templates, and the swift transition from the cubic phase to a hexagonal phase leads to the stable growth of hexagonal nitrides. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…The GaN E 2 H and SiC TO Raman peak positions are known to be related to their respective residual stresses . Figure shows the variation in GaN and SiC residual stresses, and GaN E 2 H full‐width half maximum (FWHM) for two types of microstructures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GaN E 2 H and SiC TO Raman peak positions are known to be related to their respective residual stresses . Figure shows the variation in GaN and SiC residual stresses, and GaN E 2 H full‐width half maximum (FWHM) for two types of microstructures.…”
Section: Resultsmentioning
confidence: 99%
“…indicates the influence of the underlying SiC residual tensile stress on the subsequent GaN deposition. It has previously been reported that adatom diffusion can be affected by strain in the film during growth . Therefore the SiC residual stress may have affected local Ga adatom diffusion and hence the growth morphology, which consequently may also affect the crystal quality of the deposited GaN.…”
Section: Resultsmentioning
confidence: 99%
“…В настоящее время предпринимаются попытки синтезировать полуполярный GaN в основном на подложках из сапфира [1], SiC [2] и кремния [3,4]. Синтез полуполярного GaN осуществляется как на подложках Si(11h) (где h = 2−7) [1,5], так и на разориентированных подложках Si(100) [6,7], а также с использованием буферных слоев 3C-SiC [8,9]. В работах [10][11][12] для синтеза полупо-…”
Section: поступило в редакцию 19 февраля 2018 гunclassified
“…Поэтому такие слои облада-ют значительной спонтанной поляризацией [9] и внутренним полем, что отрицательно сказывается на работе светоизлучающих устройств. Поэтому в последнее время предпринимаются попытки получения тонких пленок нитридов, в которых ростовая полярная ось была бы наклонена как можно ближе к поверхности подложки, для чего используются кремниевые пластины с отличной от 111 ориентации [10][11][12].…”
Section: Introductionunclassified